Failure Mechanism of Two-Phase Syntactic Foam Polymer Composites under Different Coating Conditions - Afolabi, Lukmon Owolabi; Ariff, Zulkifli Mohamad; Abdul Mutalib, Nor Azaniza (International Journal of Integrated Engineering, 2019)
In this study, the impact of coated hollow microsphere (HMs) on syntactic foams (SFs) failure analysis is performed. The HMs was made from polystyrene beads and were coated with CaCO3 and cementite powder to produce the SFs by Vacuum Assisted Mould Fill Technique (VAMFT). The morphological analysis was performed using Scanning Electron Microscope (SEM) and the compressive test conducted using INSTRON 5982 machine model. From the results, the HMs failure mechanism showed the cementite surface coating enhanced the shell-rigidity by 65%. The physical and compressive properties of the SFs increased with increase in % vol. fraction of the HMs. The SFs compressive modulus, flexural strength and tensile strength for the CaCO3 and cementite specimen are 470, 44, 36 MPa and 582, 48, 41 MPa, respectively. The energy absorption characteristic of the SFs was enhanced by 14% and 25% for the CaCO3 and cementite HMs surface coating, respectively. But the optimal concentration for the SFs was 20% vol. weight for both HMs coating.